2011
DOI: 10.4103/0253-7613.83134
|View full text |Cite
|
Sign up to set email alerts
|

Propofol-induced violent coughing in a patient with Becker′s muscular dystrophy

Abstract: Propofol anesthesia is often associated with decreased incidence of gagging, coughing or laryngospasm, and provides intense suppression on airway reflex during tracheal intubation and laryngeal mask airway insertion. Propofol pretreatment is also effective in reducing the occurrence of opioid-induced coughing. These benefits are often attributed to bronchodilator and sedative effects of propofol. However, severe coughing following sedative doses of 1% propofol has not been reported so far. We report a rare cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…There are few reports of cough reflex due to propofol, and it is considered a rare side effect. Case reports involving severe cough attacks during propofol anesthesia have been reported [ 7 , 8 ]. However, pentazocine is an analgesic to suppress coughing during the use of narcotics such as fentanyl [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are few reports of cough reflex due to propofol, and it is considered a rare side effect. Case reports involving severe cough attacks during propofol anesthesia have been reported [ 7 , 8 ]. However, pentazocine is an analgesic to suppress coughing during the use of narcotics such as fentanyl [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Complications during anesthesia, particularly during induction, include coughing and hiccups, which can induce body movements during oocyte retrieval and increase the risk of intra-abdominal organ damage due to semi-blind vaginal puncture into the abdominal cavity. Although complications such as coughing and hiccups under general intravenous anesthesia have been reported [7][8][9], there are no reports of such complications associated with anesthesia during oocyte retrieval.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, when TIVA was used as the only anesthetic technique, the occurrence of postoperative respiratory depression may increase in BMD patients due to high sensitivity to opioids and muscle relaxants. Moreover, propofol may lead to profound hypotension, reduced organ perfusion, and violent coughing[ 14 ]. Due to high sensitivity and prolonged duration of action of muscle relaxants in muscular dystrophy patients, it is even suggested that muscle relaxants should be avoided[ 2 ].…”
Section: Discussionmentioning
confidence: 99%